An efficient method for minimum zone cylindricity error evaluation using kinematic geometry optimization algorithm. (March 2019) - Zheng, Peng; Liu, Dongliang; Zhao, Fengxia; Zhang, Linna
Highlights: A method for minimum zone cylindricity error evaluation using KGOA is proposed. It is used to evaluate the geometric features of cylindrical engineering parts. An efficient approach for extracting feature points is also proposed. This method would greatly reduce the calculating times of evaluation. Experimental results validate the accuracy and feasibility of KGOA. Abstract: Cylindricity error evaluation is necessary to verify the cylindrical product function and to control the manufacturing process. This paper proposes a novel method for minimum zone cylindricity error evaluation based on kinematic geometry optimization algorithm (KGOA). The proposed method shows excellent performance in the cylindricity error evaluation process. First, the theoretical basis and representation for the minimum zone programming evaluation model are presented. Next, a new approach for extracting feature points is proposed using projective transformation and convex set construction. Instead of all measured points, the extracted feature points are used for the cylindricity error evaluation. On comparing the proposed method with other existing methods based on some literature data sets, agreement or improved solutions are obtained. The simulation and experiment results show that the proposed method can achieve optimum solutions accurately and improve the implementation efficiency. Compared with the commercial software of Coordinate Measuring Machine, the proposed method can reduce the average calculating time by half while retaining the accuracy of evaluation results. The basis of this method can also be applied for other geometrical error evaluation in engineering metrology.